Mapping Environmental and Socioeconomic impacts of hydrometeorological hazards across Central America. Study case: Honduras - Alfaro Martínez, Eric J. (2018)
Hydrometeorological hazards have historically affected Central America and significantly impacted the isthmus. However, the spatial distribution of those impacts is heterogeneous and depends on several factors, such as storm trajectories and community vulnerability. To address the spatial distribution of impacts related with historical events, Honduras was used as a case study. This paper was aimed at identifying the municipalities most impacted by the hydrometeorological events and at studying their correlation with socioeconomic variables. Impacts recorded from 1919 to 2012 were collected from the DesInventar and EM-DAT databases. Data was georeferenced using a Geographical Information System and the information was disaggregated at local government scale. Spearman spatial correlation were calculated between physical variables and socioeconomic indices. The municipalities that reported more impacts included La Ceiba, Choluteca, Francisco Morazán and Yoro. Three hazards were found and the most important regarding impacts: cold fronts or outbreaks, tropical cyclones and easterly waves. The first type was more common during boreal winter, while the last two hazards were normally found during boreal spring-summer-autumn. Population and poverty were the social variables with the highest correlation with impacts. The analysis showed that spatial distribution of impacts related with hydrometeorological causes cannot be explained solely by climate causes. Therefore, other variables, such as socioeconomic should also be considered in analyses of these types of impact.